طرق وآليات تفعيل حقوق اليتيم في المجتمع الأفغاني: Methods and Mechanisms for Activating Orphan Rights in Afghan Society - Azimi, Rahmatullah; fettane, Amar (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يتناول البحث "طرق وآليات تفعيل حقوق اليتيم في المجتمع الأفغاني" ويهدف إلى تقديم حلول شاملة لضمان حياة كريمة للأيتام من خلال تعزيز القوانين والتشريعات، حيث يواجه الأيتام تحديات متعددة نتيجة ضعف آليات تنفيذ القوانين والرقابة عليها. يعتمد البحث على المنهج الوصفي التحليلي لدراسة الواقع الحالي، والمنهج المقارن لاستنباط أفضل الممارسات، والمنهج الميداني لجمع البيانات. وتوصلت الدراسة إلى أن تفعيل حقوق الأيتام يتطلب إصلاحات قانونية وإدارية، وتوفير دعم شامل، وتعزيز الوعي المجتمعي لضمان دمجهم بفاعلية واستدامة في المجتمع. ABSTRACT The study examines "Methods and Mechanisms for Activating Orphan Rights in Afghan Society" and aims to provide comprehensive solutions to ensure a dignified life for orphans through the enhancement of laws and regulations. Orphans face multiple challenges due to weak enforcement mechanisms and lack of oversight. The research adopts a descriptive-analytical approach to study the current reality, a comparative approach to derive best practices, and a field-based approach to collect data. The study concludes that activating orphan rights requires legal and administrative reforms, the provision of comprehensive support, and the enhancement of community awareness to ensure their effective and sustainable integration into society.